Dostoevsky. The miraculous years, 1865-1871 - Frank, Joseph, 1918-2013. (Princeton, N.J. : Princeton University Press, 1995)
This volume, the fourth of five in Joseph Frank's widely acclaimed biography of Dostoevsky, covers the six most remarkably productive years in the novelist's entire career.
Includes bibliographical references (p. 505-515) and index.
Keywords: Dostoyevsky, Fyodor, -- 1821-1881.; Novelists, Russian -- 19th century -- Biography; Russia -- Intellectual life -- 1801-1917.